New Product Development and New Business Model Canvas for Geulis Travel - Hudapitra, Muhammad; Larso, Dwi (The Indonesian Journal of Business Administration, 2016)
Abstract. Everyone needs transportation because it enables trading or socialization between persons, which is essential for the development of civilization.. Jatinangor is a city of education because there are many universities, so there are 50.000 college student associated with those universities. Based on this opportunity, Trans Geulis Indonesia Company was founded to serve the need. Trans Geulis Indonesia is Transportation Company who provides shuttle service Bandung Jatinangor and Rent car. Currently this company faces several issues: failure to penetrate in rented car market, failure to make quick decision, financial failure, unpredicted fuel price and political instability, and holiday season for college students in Jatinangor. The main issue is the holiday season, because in that time, many students who are the biggest customers are not using Trans Geulis Indonesia shuttle services. Based on those issues, Trans Geulis Indonesia’s objective is increasing the revenue and creating a new business model canvas to develop the business.. The data of internal assessment are analyzed through Business Model Canvas analysis, and the external assessment is analyzed through use PESTEL analysis and Porter 5 force. In order to solve the root cause, Trans Geulis Indonesia needs to implement solution by developing new business model. This business development analyze through renew the old business model canvas in customer segment, value proposition, channel ,cost structure, and revenue stream. There is also a new business in developing the product, it is rent Elf and bus service. Keywords : transportation,car, business model